THE RELATIVE CHARACTERISTIC OF ORTHOSTATIC REACTIONS OF ARTERIAL PRESSURE AND HEART RATE VARIABILITY AT PERSONS WITH ISOLATED AND COMBINED AN OSTEOARTHROSIS AND AN ARTERIAL HYPERTENSIA - Soldatenko, I.V.; Lysenko, N.V.; Iabluchanskyi, M.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The relative characteristic of orthostatic reactions (OR) of blood pressure (BP) and heart rate variability (HRV) in 90 patients at the age of 58±10 years with isolated and combined osteoarthritis (OA) and arterial hypertension (AH) is spent. ОА, АH and combined ОА+АН are characterised by identical patterns in ОR a BP and measures of HRV, and also measures HRV in assay with breath modulation that testifies in favour of identical system neurohumoral mechanism of development ОА and АH. Lower value ТР and higher LF/HF in groups of patients ОА+АГ against groups of patients with isolated ОА and АH and their less awake reactions on orthostate and in assay with breath modulation, testify to more serious flow combined OA+AH in comparison with isolated ОА and АH.